PETA PERSEPSI KONSUMEN TERHADAP ATRIBUT RUMAH TINGGAL DI SURABAYA (Jurnal Manajemen dan Kewirausahaan, 2013)
This study aimed to map consumer perceptions of residential attributes, namely the neighbourhood, location, price, and physical. The research method was descriptive that data obtained through questionnaires to sample number of 384 respondents in some residential estate of East and West Surabaya. The results showed that consumers prioritize neighbourhood attributes of public facilities (water, electricity, telephone) and social amenities (markets, transportation, places of worship). The most priority of location was the distance to school and traditional markets.